A formação da convicção do magistrado: da efetividade processual à análise judicial da prova e as máximas de experiência - a influência da filosofia e das ciências auxiliares do direito nessa operação - Belucci, Gustavo Henrique Pacheco (2014)
The central theme to be developed lies in the formation of the conviction of the magistrate and the elements that make this convincing, given by the system (procedural factors), and the related sciences of law, such as philosophy, sociology, logic, mathematics, etc. (extra procedural factors), in prove that these factors combine. The working part of the effectiveness of the process, which will be studied in order to ensure conditions conducive to accurate and complete reconstruction of the relevant facts of the case and also the influence of the Constitution, to study how the court system has about the construction of the conviction of the magistrate, grounded in the general theory of proof and factors extra procedurals, philosophical and logical to then utters decision, which will produce not only the simple application of the law, but a complex theory which is the formation of the conviction of the judge. The factors are divided trainers conviction on procedural and extra procedurals, these being internal and external. By procedural factors may be indicated in the evidence related species by the system, and how extra procedurals, those internal factors (rules are studied by the integration of the right) and external training of conviction (culture and values). These extra procedurals external elements shall be studied based on a philosophical concept. It was decided, accordingly to the study, and the philosophy of law of Miguel Reale, Lourival Vilanova e Paulo de Barros Carvalho, the doctrine of David Hume (eighteenth century), and John Stuart Mill (nineteenth century) in his work Treatise of Human Nature and On Liberty, respectively, for evidence the influence of the external environment and the society on people and consequently, the formation of the formation of the conviction of the Magistrate, relating brief case study at the end of chapters four and five. It will be presented, by the end of the chapters, the correspondence of the themes with the Project of New CPC (PL 8.046/2010). For these motives, the theme chosen is: The formation of the conviction of the magistrate - the effectiveness of judicial review of the evidence and the maxims of experience. The influence of philosophy and the sciences auxiliary of law in this operation